Multiple Dental and Skeletal Abnormalities in an Individual with Filippi Syndrome - Meera Sandhu; Pooja Malik; Rooposhi Saha (Hindawi Limited, 2013)
Filippi syndrome is an autosomal recessive condition characterized by variable soft tissue syndactyly of the fingers and toes, microcephaly, pre- and postnatal growth retardation, mildly abnormal craniofacial appearance, and mental retardation. We report on a child with Filippi syndrome who shows syndactyly of fingers, severe postnatal growth retardation, postnatal microcephaly, and moderate to severe mental retardation. In addition, there is a mildly dysmorphic face along with ocular and a number of dental abnormalities. Radiologically, hands demonstrate bony syndactyly, without any hypoplasia of bones. This phenotype can easily be classified in the group of craniodigital syndromes, but it is difficult to make a more clearly defined diagnosis, based on other minor anomalies, because of the presence of overlapping features. On the basis of various pathognomic features, we conclude that our patient could be an additional case of Filippi syndrome. Moreover, newly recognised features in this patient may be due to variability in phenotypic expression.